The Social Arithmetics Module Based on Islamic Values and Realistic Mathematics Education to Improve Students’ Problem-Solving Skills - Rakhmawati, Intan Aulia (Edumatika, 2023)
Mathematics learning must be made more exciting and meaningful to overcome the perception that mathematics is a tricky subject. Students must be facilitated to build their knowledge through mathematics learning linked to realistic problems and integrated with Islamic values so that they can solve relevant daily problems. This research aims to develop a Social Arithmetic module based on Islamic values ​​and Realistic Mathematics Education (RME) to help junior high school students improve their problem-solving skills. This research uses R&D with the ADDIE development model. The development of the mathematics module consists of three stages, namely the preliminary, development, and evaluation stages. The resulting module prototype has been assessed as valid by material and media experts. Meanwhile, based on student and teacher responses to the questionnaire, the module was proven suitable for use in mathematics learning. In addition, the results of the paired t-test stated that the module was effective in improving students' problem-solving skills. Therefore, this research concluded that the Social Arithmetics module based on Islamic values ​​and RME that were developed has met the valid and practical criteria and has proven effective in improving the problem-solving abilities of seventh-grade junior high school students.